2019
DOI: 10.1002/hep.30275
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Tuning of Sirtuin 1 Expression Is Essential to Protect the Liver From Cholestatic Liver Disease

Abstract: Cholestasis comprises aetiologically heterogeneous conditions characterized by accumulation of bile acids in the liver that actively contribute to liver damage. Sirtuin 1 (SIRT1) regulates liver regeneration and bile acid metabolism by modulating farnesoid X receptor (FXR); we here investigate its role in cholestatic liver disease. We determined SIRT1 expression in livers from patients with cholestatic disease, in two experimental models of cholestasis, as well as in human and murine liver cells in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 46 publications
2
40
2
Order By: Relevance
“…27 Regulation of SIRT1 expression is essential to protect the liver from cholestatic liver disease. 28 Song et al suggested that metformin alleviates hepatic steatosis through PRKA-independent, SIRT1-mediated effects on the autophagy machinery. 29 Dioscin markedly prevented NAFLD by adjusting lipid metabolism via the SIRT1/AMPK signal pathway, which should be considered as a new therapeutic candidate for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…27 Regulation of SIRT1 expression is essential to protect the liver from cholestatic liver disease. 28 Song et al suggested that metformin alleviates hepatic steatosis through PRKA-independent, SIRT1-mediated effects on the autophagy machinery. 29 Dioscin markedly prevented NAFLD by adjusting lipid metabolism via the SIRT1/AMPK signal pathway, which should be considered as a new therapeutic candidate for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…91 Dysregulation of glycolysis, triglyceride synthesis, and lipid metabolism occurs because of decreased expression of sirtuin, PGC-1α, and lower concentrations of NAD þ . 92 The analysis of senescence markers in aged mice showed upregulation of p16 and downregulation of STIR1 in the liver tissue; interestingly, the latter is known to regulate liver regeneration and bile acid metabolism by modulating farnesoid X receptor. 93 On the contrary, hepatocytes are relatively resistant to telomere shortening, 94 maybe due to the high expression levels of telomerase.…”
Section: Aging-related Molecular Alterations In Liver Diseasesmentioning
confidence: 99%
“…Previous studies have demonstrated that increases in Sirt1 suppress PAFR expression in platelets and that increases in Sirt1 limits cholestasis 26,27 . To investigate whether Sirt1 was associated with decreased PAFR in colitis‐induced liver inflammation, we measured Sirt1 gene and protein levels in the livers during colitis‐induced inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, in the Huh7 cells, overexpression of PAFR had an additive effect to LPS‐induced Sirt1 increases. This may indicate that downregulation of PAFR is important in fine tuning or restricting Sirt1 responses, which is important in protecting the liver from cholestasis 27 . It is unclear why PAFR protein localizes at the portal triad, comprising of the portal artery, portal vein, and bile duct, 40 during colitis, although this may be driven by localized ischemia caused by endotoxin exposure 49 .…”
Section: Discussionmentioning
confidence: 99%